Stress and epenthesis in a Jordanian Arabic dialect: Opacity and Harmonic Serialism - Abu-Abbas Khaled H.; Al-Zoubi Abdul Aziz (Open Linguistics)
This article investigates aspects of stress assignment in a Jordanian Arabic dialect (JA). Cases of opaque stress are discussed with reference to Harmonic Serialism (HS) within the framework of Optimality Theory (OT). Two sources of opaque stress are under consideration. On the one hand, a syllable in an antepenultimate position is stressed where a Heavy penultimate is expected to receive stress. On the other hand, a light penultimate syllable is stressed where an antepenultimate Heavy syllable is expected to receive stress. All cases of opaque stress in the dialect involve an epenthetic vowel in the penultimate syllable or in the ultimate syllable in the two structures, respectively. An account of such opaque structures requires faithfulness to the location of stress before epenthesis; a scenario perfectly handled with reference to HS.